PROVISION OF SUPPLEMENTARY FOOD FOR SASIGO AND BISCUIT IN INCREASING THE WEIGHT OF CHILDREN : A COMPARATIVE STUDY IN NAMBO PRIMARY HEALTH CARE IN KENDARI CITY: Supplementary Food for Children - Rasyid, Mariyatni; Timbul Supodo; Banudi, La (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background:The prevalence of community nutritional status in the Kendari City area in 2016 was 0.23%. In 2017, the prevalence of nutritional status decreased in 0.13% and then increased in 2018 by 4.67%. in 2019, the prevalence of nutritional status decreased by 2.25% . Thus, children under five have nutritional status did not reached the target This study aimed to understand the effect of giving the sasigo and biscuit on increase the children’s weight in Nambo Primary Health Care in Kendari City. Methods:The type of research in this research is pre-experimental research with a Pre Test - Post Test design. This research was conducted in the working area of ??Nambo Peimary Health Care, Kendari City. Population were 227 and a sample was 67 malnourished toddlers in 2019. Result:Based on the independent sample test output in the Equal Variances Assumed section on Local PMT (BageaSasigo), it is known that the sig (2-tailed) value is 0.001 <0.05, so Ha is accepted so that there is a significant difference between the provision of local PMT (BageaSasigo). Whereas in the Government PMT (biscuits) it is known that the sig (2-tailed) value is 0.000 <0.05, so Ha is accepted so that there is a significant difference between the provision of government PMT (biscuits) to toddlers in the Work Area of ??the PuskesmasNambo, Kendari City. Conclusion:Provision of Local PMT (Bagea Sasigo) and Government PMT (Biscuits) for toddlersBefore giving the intervention it was not effective while after giving the intervention it was effective and significant.